An imidazolium-modified chiral rhodium/diamine-functionalized periodic mesoporous organosilica for asymmetric transfer hydrogenation of α-haloketones and benzils in aqueous medium. Issue 20 (12th August 2016) - Zhou, Feng; Hu, Xiaoying; Gao, Ming; Cheng, Tanyu; Liu, Guohua
Abstract : An imidazolium-modified chiral rhodium/diamine-functionalized periodic mesoporous organosilica is developed, which greatly promotes asymmetric transfer hydrogenation of α-haloketones and benzils in aqueous medium. Abstract : The use of a hydrophobic, imidazolium-functionalized periodic mesoporous organosilica for immobilization of chiral organometallic complexes as a heterogeneous catalyst is highly desirable as this catalyst can greatly promote an aqueous organic transformation due to its hydrophobic function and phase-transfer feature in an aqueous medium. Herein, by utilizing a three-component co-condensation strategy, we conveniently incorporate 1, 2-bis(triethoxysilyl)ethane, ( R, R )-4-((trimethoxysilyl)ethyl)phenylsulfonyl-1, 2-diphenylethylene-diamine and 1, 3-bis(3-(triethoxysilyl)propyl)-1 H -imidazol-3-ium iodide within its silicate network, which is coordinated with (Cp*RhCl2 )2, leading to an imidazolium-modified chiral rhodium/diamine-functionalized periodic mesoporous organosilica. A solid-state carbon spectrum discloses its well-defined chiral rhodium/diamine active species, and its X-ray diffraction; nitrogen adsorption–desorption measurement and transmission electron microscopy images reveal its ordered dimensional-hexagonal mesostructure. As a bifunctional heterogeneous catalyst, this periodic mesoporous organosilica significantly boosts asymmetric transfer hydrogenation of α-haloketones and benzils in water, where the hydrophobic periodic mesoporous organosilica, phase-transfer-featured imidazolium-functionality, and the confined chiral organorhodium catalytic nature are responsible for its catalytic performance. Furthermore, the catalyst can be recovered and recycled seven times without the loss of its catalytic activity, making it an attractive heterogeneous catalyst for asymmetric transfer hydrogenation in an environmentally friendly manner.